Effect of Supports and Promoters on the Performance of Ni‐Based Catalysts in Ethanol Steam Reforming. Issue 4 (3rd March 2020) - Phung, Thanh Khoa; Pham, Thong Le Minh; Nguyen, Anh-Nga T.; Vu, Khanh B.; Giang, Ha Ngoc; Nguyen, Tuan-Anh; Huynh, Thanh Cong; Pham, Hong Duc
Abstract: Ethanol steam reforming (ESR) is one of the potential processes to convert ethanol into valuable products. Hydrogen produced from ESR is considered as green energy for the future and can be an excellent alternative to fossil fuels with the aim of mitigating the greenhouse gas effect. The ESR process has been well studied, using transition metals as catalysts coupled with both acidic and basic oxides as supports. Among various reported transition metals, Ni is an inexpensive material with activity comparable to that of noble metals, showing promising ethanol conversion and hydrogen yields. Additionally, different promoters and supports were utilized to enhance the hydrogen yield and the catalyst stability. This review summarizes and discusses the influences of the supports and promoters of Ni‐based catalysts on the ESR process. Abstract : Hydrogen produced from ethanol steam reforming (ESR) can be an excellent alternative to fossil fuels. The ESR process has been well studied, also using transition metals as catalysts coupled with both acidic and basic oxides as supports. This review discusses the influences of the supports and promoters of Ni‐based catalysts on the ESR process.